Synthesis and properties of some 3-(5-(4-methoxyphenyl)pyrazol-3-yl)-6-R-[1,2,4]triazolo[3,4-b][1,3,4]thiadiazoles - S. O. Fedotov; A. S. Hotsulia; O. I. Panasenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
Pyrazole and 1,2,4-triazole derivatives play an important strategic role in modern medicine and pharmacy. This fact is due to the significant possibilities of chemical modification and significant pharmacological potential among the derivatives of these heterocycles. The introduction of 1,2,4-triazole and pyrazole fragments into the structure of new substances allows to influence the formation of a certain type of activity. The structural combination of these heterocycles in one molecule increases the likelihood of interaction with various biological targets. At the same time, the creation of condensed systems involving 1,2,4-triazole is undoubtedly scientifically attractive and promising.